ЦЕНТРАЛЬНО-СХІДНА ЄВРОПА ЯК ІСТОРИЧНИЙ РЕГІОН: ЗМІСТ ТА ЕВОЛЮЦІЯ КОНЦЕПЦІЇ (Zaporizhzhia Historical Review, 2021)
The article deals with the consideration of the conception of Central-Eastern Europe as a historical region. The author traces the stages of evolution of the notion and gives an up-to-date understanding of the conception ìCentral-Eastern Europeî in the World and Ukrainian historiography, shows common historical, political and cultural characteristic features of the region. The methodological aspects of applying the conception of Central-Eastern Europe as a historical region when studying transformation processes on the edge of the 1980-1990ties are singled out in the article.